2012
DOI: 10.4103/0973-1296.99287
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, nutritional value, and antioxidant activities of eight mulberry cultivars from China

Abstract: Background:Mulberry (Morus, Moraceae) is widely distributed in the temperate, subtropical, or tropical regions of the world, while there are no conclusive reports on the chemical composition, nutritional value, and antioxidant properties of mulberry cultivars from China.Objective:To investigate chemical properties and to determine proximate nutritive compounds of the eight mulberry cultivars.Materials and Methods:Chemical properties (including moisture, ash, total dry matter, total soluble solids, pH, and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 31 publications
13
46
0
Order By: Relevance
“…A similar trend was obtained for MLs2, but its content in polysaccharide had a little lower when compared with MLs1. These results were in correspondence with those previously reported [38]. As shown in Table 3, the content of polysaccharides showed MLs1.10 and MLs1.8 treated with SG increased considerably, with different significant value p<0.05 from 96.86 mg/g (D115) to 157.68 mg/g (D10).…”
Section: Effect Of Sg On Polysaccharides Contentssupporting
confidence: 82%
“…A similar trend was obtained for MLs2, but its content in polysaccharide had a little lower when compared with MLs1. These results were in correspondence with those previously reported [38]. As shown in Table 3, the content of polysaccharides showed MLs1.10 and MLs1.8 treated with SG increased considerably, with different significant value p<0.05 from 96.86 mg/g (D115) to 157.68 mg/g (D10).…”
Section: Effect Of Sg On Polysaccharides Contentssupporting
confidence: 82%
“…In China, mulberry leaves are also used in several traditional Chinese medicine formulas. Mulberry leaf and fruit extracts are reported to have beneficial effects on human health (Liang et al 2012;Lim et al 2013;Mudra et al 2007); however, their material substances and mechanisms of action have not been well studied. In this study, we found that MLP could delay aging using the short-lived nematode C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry fruit, bark, roots, and leaves have been used as folk medicines in China. Mulberry leaf is an important ingredient in some traditional Chinese medicinal formulas and is considered to have high nutritional value and antioxidant activity, which could be developed for use in foods benefiting human health (Liang et al 2012). Combined extracts from mulberry fruits and leaves was demonstrated to improve obesity-related inflammation and oxidative stress resistance in obese mice (Lim et al 2013).…”
mentioning
confidence: 99%
“…However currently and especially due to its nutritive value, mulberry fruits are consumed as both fresh and processed products, such as juices, fruit salads and dried fruits (Calin- Sanchez et al, 2013). Recently, the production and consumption of mulberry fruits are rapidly increasing because of their aromatic taste, nutritional value, bioactive compound content and biological activities (Liang et al, 2012).…”
mentioning
confidence: 99%
“…Thanks to these health-promoting compounds mulberry fruits are traditionally used as a worming agent and a laxative, odontalgic, anthelmintic, expectorant, hypoglycemic, and emetic agent; in traditional Chinese herbal medicine, mulberry fruit has been used as a folk remedy to treat oral and dental diseases, diabetes, hypertension, arthritis and anemia (Liang et al, 2012).…”
mentioning
confidence: 99%